Management Development for Improving Service Quality in Mba Fhera's Grilled Chicken MSME - Ita Purnama; Ashabili Shainalli; Risma Damayanti (Journal of Economics, Management and Accounting (JEMA), 2024)
This study aims to analyze the influence of management development on improving service quality in Mba Fhera's Grilled Chicken MSME. A descriptive qualitative approach with a case study method was used. Data were obtained through observation, in-depth interviews with the business owner, and field documentation. The findings indicate that management development encompassing resource management, operational systems, and service strategies significantly impacts service quality enhancement. Key success factors for this MSME include adaptability to technology, consistent product quality, and commitment to customer service. This study provides practical contributions for MSME actors to enhance competitiveness through adaptive and sustainable managerial strategies.